EMBR-01. CLASS I HDAC INHIBITORS AND PLK1 INHIBITORS SYNERGIZE IN MYC-AMPLIFIED MEDULLOBLASTOMA. (1st June 2021) - Valinciute, Gintvile; Ecker, Jonas; Selt, Florian; Hielscher, Thomas; Schmidt, Christin; Sigaud, Romain; Ridinger, Johannes; Gatzweiler, Charlotte; Picard, Daniel; Oppermann, Sina; Blattner-Johnson, Mirjam; Jones, David T W; et al.
Abstract: Background: Medulloblastoma (MB) is one of the most common malignant pediatric CNS tumors. Patients with Group 3 MBs harboring MYC amplification exhibit low survival rates. Surviving patients suffer from therapy-induced sequelae, which calls for new targeted therapy strategies. We and others have previously shown the sensitivity of MYC -amplified MB to class I histone deacetylase (HDAC) inhibition. After demonstrating that the MYC target gene PLK1 is significantly downregulated upon class I HDACi treatment, we hypothesized that inhibition of both HDACs and PLK1 could have synergistic effects. Methods: Cell metabolic activity changes upon HDAC and PLK1 inhibitor treatment were measured in MYC -amplified and non-amplified MB cell lines, as well as in an additional MYC -inducible cell line. The interaction effect of both inhibitors was determined by computation of the combination index (CI) using the Chou-Talalay method. Results were validated assessing cell viability, cell cycle, and apoptosis induction. Transcription profile changes after combination treatment were evaluated. Results: MYC -amplified MB cell lines were more sensitive than non-amplified cell lines to PLK1i treatment, showing IC50 in clinically achievable concentration ranges. Inhibition of class I HDACs and PLK1 synergistically reduced cell metabolic activity in lower concentrations in MYC -amplified compared to non-amplified MB cell lines. We also observed a significant loss of viability and cells in G1 phase, as well as induction of apoptosis after combination treatment in MYC -amplified cells. MYC target gene sets were significantly downregulated in the MYC -amplified cell line HD-MB03 after treatment with combination. We demonstrated reduction of MYC protein levels upon PLK1i treatment. In vivo evaluation of combination treatment using orthotopic Group 3 MYC -amplified MB PDX models is ongoing. Conclusion: Our data suggest that MYC -amplification is a predictive marker for PLK1i treatment in MB. The combination of HDACi and PLKi could be a candidate therapy for future clinical trials for MYC -amplified group 3 MB.